Toward More Effective and Legitimate Institutions to Handle Problems of Justice in Solomon Islands - Porter, Douglas; Isser, Deborah; Venning, Philippa (World Bank, Washington, DC, 2015)
This policy note summarizes key lessons and conclusions from the World Bank's engagement in Solomon Islands under the justice for the poor program, which has been active in that country since 2009. It interprets what has been learned in connection with a question posed at the start of this program: what can be done to support more effective and legitimate institutions to handle problems of justice in Solomon Islands?. To answer this question, the note is organized around a set of three questions. First, what are Solomon Islanders' main justice concerns? Second, how are these concerns being handled today, to what extent are people satisfied, and why? Third, what can Solomon Islanders and their development partners do to improve justice outcomes? This note is an effort to shift the standard discourse on building justice institutions to a problem driven approach that seeks to grapple with the contextual peculiarities of Solomon Islands. The approach, which this note aims to illustrate, begins with an assessment of how problems are experienced by citizens and then examines how these issues are being handled by public authorities, whether secular, religious, chiefly, or kastom in nature. It then considers the conditions under which these authorities may work differently and also the likelihood that powerful players and citizens will invest in the forms of institutions needed to incrementally, but appreciably, deliver better results.